Effect of Elevated Serum Bile Acid Levels in Intrahepatic Cholestasis of Pregnancy on Antenatal and Postnatal Outcomes; Prospective Cohort Study - Iftikhar, Mahrukh; Alia Bano; Ayub, Bushra (Indus Journal of Bioscience Research, 2025)
Study objective: To evaluate the association of IHCP with antenatal and postnatal outcomes, aiming to reduce the disease-related morbidity and mortality. Design: Prospective cohort study. Setting: Gynaecology and Obstetrics unit of Patel hospital, Karachi. Material and Methods: .Data were collected from pregnant patients with pruritus without rash, elevated liver enzymes, and serum bile acids ≥19 µmol/L. Disease severity was classified by bile acid levels. Management included ursodeoxycholic acid, antihistamines, and emollients, with follow-up testing after 7–14 days. Delivery decisions were based on symptoms, bile acid trends, and pregnancy risk factors. Maternal and neonatal outcomes were recorded using structured questionnaire. Studied parameters included timing of symptom onset, diagnosis of disease, time and mode of delivery, liquor colour, neonatal outcomes, birth weight and NICU admission. Results: 36 patients were diagnosed with IHCP based on elevated serum bile acid levels. Most patients had singleton pregnancies (94.4%), with one twin and one triplet pregnancy. The mean maternal age was 26.14 years. Primigravida and multigravida women constituted 50% each, and 33.6% of multigravidas had a prior history of IHCP. Pruritus typically appeared between 29–34 weeks (median 32 weeks). ALT and AST elevation was noted between 30–36 weeks (median 33.5 weeks), while serum bile acids were elevated between 32–36 weeks (median 34.5 weeks). Based on bile acid levels, 61.1% had mild IHCP (19–39 μmol/L), 27.8% moderate (40–99 μmol/L), and 11.1% severe (≥100 μmol/L). The median gestational age at delivery was 37 weeks in mild and moderate IHCP and 36.3 weeks in severe cases. Delivery decisions were individualized. Vaginal delivery occurred in 36.1%, while 41.7% underwent elective and 22.2% emergency caesarean section. Induction of labour was performed in 13 patients, with non-progress of labour being the most common indication for emergency caesarean section. A total of 39 live-born neonates were delivered. The mean birth weight was 2.3 kg, with 58.9% weighing 2.5–3.5 kg. Meconium-stained liquor was observed in 25.6%, with no cases of meconium aspiration. NICU admission was required in 25.6%, primarily for transient tachypnea of the newborn and respiratory distress syndrome. Conclusion: This study reinforces the importance of serum bile acid estimation as a primary diagnostic and prognostic tool in IHCP and highlights the benefits of structured monitoring and timely intervention in improving fetomaternal outcomes.